Impact of Cell-of-Origin on Outcome of Patients With Diffuse Large B-Cell Lymphoma Treated With Uniform R-CHOP Protocol: A Single-Center Retrospective Analysis From North India - Gogia, Ajay; Nair, Sukesh; Arora, Shalabh; Kumar, Lalit; Sharma, Atul; Gupta, Ritu; Biswas, Ahitagni; Mallick, Saumyaranjan (Frontiers in Oncology, 2021)
Introduction:There is scarcity of data from Indiaon the impact of cell of origin (COO) on outcomes of Diffuse Large B-cell Lymphoma (DLBCL). This study was conducted to evaluate the impact of COO on outcomes of DLBCLpatientstreated with uniform rituximab, cyclophosphamide, doxorubicin, vincristine and prednisolone (RCHOP) protocol. Materials and Methods: This retrospective analysis includedpatients who received uniform RCHOP chemoimmunotherapy during the study period (2014-2020) at the Department of Medical Oncology at All India Institute of Medical Sciences (AIIMS), New Delhi, India .The patients were classified as germinal centre B-cell like (GCB) or activated B-cell (ABC) type using the Hans classification. Results:Four hundred seventeen patients with median age 48 (range18-76) yearsand a male-female ratio of 2:1 were included in the analysis. B-symptoms and bulky disease were seen in 42.9% and 35.5% Extranodal involvement was seen in 50.8% of cases. ECOG performance status (0-2) was present in 65%, and 51% presented with advanced disease. GCB subtype was seen in 43% and 47% were ABCtype. Low and intermediate-risk international prognostic index (IPI)score was seen in 76% of cases. The overall response rate to RCHOP was 85.8 %, including a complete response rate of 74.8 %.After a median follow-up of 30 months, the 3-year event free survival (EFS) survival and overall survival (OS) were 80 % and 88 % respectively. Presence of B symptoms and poor ECOG performance status (3-4) were associated with inferior CR rate. Low albumin (<3.5 gm/dl), age >60 years, bulky disease, and extranodal involvement were associated with inferior EFS, whereas a high IPI risk score was associated with an inferior OS. EFS and OS were not significantly different between the GCB and ABC subtypes. Grade III/IV anemia, neutropenia, and thrombocytopenia were seen in 7.6%, 13.6%, and 2.7% of patients respectively. Febrile neutropenia was seen in 8.9 % of patients and there were 4 treatment-related deaths. Conclusions:Cell of origin for DLBCL has no impact on CR, EFS and OS if patients are appropriately treated with standard doses and frequency of RCHOP. RCHOP is well tolerated in our patients and results are comparable with the western data.